No metagenomic evidence of tumorigenic viruses in cancers from a selected cohort of immunosuppressed subjects - Passaro, Nunzia; Casagrande, Andrea; Chiara, Matteo; Fosso, Bruno; Manzari, Caterina; D’Erchia, Anna Maria; Iesari, Samuele; Pisani, Francesco; Famulari, Antonio; Tulissi, Patrizia; Mastrosimone, Stefania; Maresca, Maria Cristina; et al. (Scientific reports, 2019)
The possible existence of yet undiscovered human tumorigenic viruses is still under scrutiny. The development of large-scale sequencing technologies, coupled with bioinformatics techniques for the characterization of metagenomic sequences, have provided an invaluable tool for the detection of unknown, infectious, tumorigenic agents, as demonstrated by several recent studies. However, discoveries of novel viruses possibly associated with tumorigenesis are scarce at best. Here, we apply a rigorous bioinformatics workflow to investigate in depth tumor metagenomes from a small but carefully selected cohort of immunosuppressed patients. While a variegated bacterial microbiome was associated with each tumor, no evidence of the presence of putative oncoviruses was found. These results are consistent with the major findings of several recent papers and suggest that new human tumorigenic viruses are not common even in immunosuppressed populations.